Professional ASP.NET 3.5 AJAX - Evjen, Bill (Wrox professional guides., 2009)
Describes how to create interactive Web applications using ASP.NET 3.5 Ajax, covering such topics as JavaScript, using the ScriptManager, working with animations, building custom controls, and testing and debugging.